2020
DOI: 10.1093/jrr/rraa123
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric comparison between volumetric modulated arc therapy planning techniques for prostate cancer in the presence of intrafractional organ deformation

Abstract: The purpose of this study was to compare single-arc (SA) and double-arc (DA) treatment plans, which are planning techniques often used in prostate cancer volumetric modulated arc therapy (VMAT), in the presence of intrafractional deformation (ID) to determine which technique is superior in terms of target dose coverage and sparing of the organs at risk (OARs). SA and DA plans were created for 27 patients with localized prostate cancer. ID was introduced to the clinical target volume (CTV), rectum and bladder t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Some investigators [ 37 , 38 ] evaluated the benefit of multi-arc VMAT plans in prostate cancer and documented their improved target homogeneity compared to single-arc plans. However, Nguyen et al [ 39 ] stated that under the condition of unrestricted control over hardware performance parameters like dose rate, MLC leaf positioning, and gantry rotation speed, a single arc could produce the same dose distribution as multiple arcs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some investigators [ 37 , 38 ] evaluated the benefit of multi-arc VMAT plans in prostate cancer and documented their improved target homogeneity compared to single-arc plans. However, Nguyen et al [ 39 ] stated that under the condition of unrestricted control over hardware performance parameters like dose rate, MLC leaf positioning, and gantry rotation speed, a single arc could produce the same dose distribution as multiple arcs.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies [ 19 , 26 ], it has been demonstrated that the probabilities of prostate motion >3 mm and >5 mm within 5 min were 1.8% and 0.0%, respectively, and that intrafraction prostate motion had a noticeable impact on some individual fractions using 2 mm PTV margins but tended to average out when considering the cumulative effect over 4–5 treatment fractions. The use of SA VMAT plans as planning strategy to shorten the delivery time has been widely recommended as well [ 34 , 37 , 38 , 42 ]. In the current study, partial 10 MV FFF SA plans allowed us to keep the mean delivery time as low as 1.5 min, with all plans delivered in less than 2 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has similarly demonstrated that IMRT therapy outperforms alternative treatment modalities [ 21 , 22 ]. Additionally, when comparing newer radiotherapy methods with the established IMRT technique, these innovations have only shown marginal improvements [ 23 , 24 ]. Subsequently, in this study, IMRT was considered the preferred choice for bladder and bowel preservation compared to VMAT.…”
Section: Discussionmentioning
confidence: 99%